2009
DOI: 10.1203/pdr.0b013e3181894a25
|View full text |Cite
|
Sign up to set email alerts
|

X-Linked Inhibitor of Apoptosis Protein Expression After Ischemic Injury in the Human and Rat Developing Brain

Abstract: X-linked inhibitor of apoptosis protein (XIAP) is a potent suppressor of neuronal death. The aim of this study was to investigate the expression of XIAP after ischemia in the human and rat developing brain. Autopsy specimens from 19 children with neuropathologic diagnosis of focal cerebral ischemic infarct were processed immunohistochemically for XIAP expression. XIAP positive cells were compared in pathologically classified acute (1-4 d), subacute (5-30 d), and chronic (months) strokes vs. age-matched control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…It has also been shown to inhibit caspase-independent cell death [Silke et al, 2001[Silke et al, , 2002. We have shown that XIAP is upregulated in the penumbra of the ischemic rat and human developing brain, and this upregulation is prolonged for up to at least 1 week after injury [Askalan et al, 2009]. For these reasons, we have extended our investigation to determine the effect of hypothermia on XIAP expression in the ischemic neonatal rat brain.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It has also been shown to inhibit caspase-independent cell death [Silke et al, 2001[Silke et al, , 2002. We have shown that XIAP is upregulated in the penumbra of the ischemic rat and human developing brain, and this upregulation is prolonged for up to at least 1 week after injury [Askalan et al, 2009]. For these reasons, we have extended our investigation to determine the effect of hypothermia on XIAP expression in the ischemic neonatal rat brain.…”
Section: Discussionmentioning
confidence: 92%
“…Female rats were allowed to deliver vaginally, and all litters were culled to 10 pups within 48 h of birth. The well-established Rice-Vannucci stroke model [Yager and Ashwal, 2009] was used to induce hypoxic-ischemic injury in the neonatal rat brain as previously described [Askalan et al, 2009]. In brief, 7-day-old rat pups were randomly assigned to either the control or cerebral hypoxia-ischemia (HI) group.…”
Section: Neonatal Stroke Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…XIAP stops both intrinsic and extrinsic apoptosis by binding to the initiator caspase (caspase-9) and halting further cleavage of downstream caspases (caspases 3 and 7) [59]. XIAP has also been shown to bind and inhibit caspases 3 and 7 directly [for a review, see [57]], and its expression has been confirmed in both rodent and human brains following ischemic injury [60]. Because XIAP acts on the caspase-dependent pathway of cell death, it may play a selective role in the protection afforded to females following early HI injury.…”
Section: Introductionmentioning
confidence: 99%
“…95 In vitro studies have identified endogenous XIAP as a critical regulator of neuronal apoptosis, 96 and data from studies of mice overexpressing XIAP have shown that increased levels of this protein confer protection against hypoxia-ischemia-induced caspase activation in both the adult 97 and neonatal brain. 98 In a model of transient cerebral ischemia in rats, XIAP overexpression increased cell survival by 5 to 6-fold and improved functional recovery. 99 Pharmacological implementation of XIAP-based neurorescuing has been successfully reported by Fan et al 100 in a model of transient brain ischemia.…”
Section: Inhibitors Of Apoptosis Proteins: the Natural Caspase Inhibimentioning
confidence: 99%